1999
DOI: 10.1038/sj.onc.1203283
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage-induced cell cycle checkpoints and DNA strand break repair in development and tumorigenesis

Abstract: Several newly identified tumor suppressor genes including ATM, NBS1, BRCA1 and BRCA2 are involved in DNA double-strand break repair (DSBR) and DNA damage-induced checkpoint activation. Many of the gene products involved in checkpoint control and DSBR have been studied in great detail in yeast. In addition to evolutionarily conserved proteins such as Chk1 and Chk2, studies in mammalian cells have identified novel proteins such as p53 in executing checkpoint control. DSBR proteins including Mre11, Rad50, Rad51, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
275
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 393 publications
(287 citation statements)
references
References 193 publications
(227 reference statements)
5
275
1
Order By: Relevance
“…In wtp53-carrying cells, ADR-induced DNA damage is known to block both G1-S and G2-M transition while direct p53 inactivation results in complete G1 depletion. 28 In murine and human wt53-carrying cells, we showed that the impairment of the ERK2 cleavage by caspase inhibitors interfered with the ADR-induced G1 arrest, slowing down the exit from the cell cycle and determining a partial depletion of the G1 phase. These results indicate that the ERK2 cleavage participates in the p53-mediated mechanisms of G1 arrest.…”
Section: Erk2 Cleavage Is Required For P53 To Inhibit Cell Proliferationmentioning
confidence: 92%
“…In wtp53-carrying cells, ADR-induced DNA damage is known to block both G1-S and G2-M transition while direct p53 inactivation results in complete G1 depletion. 28 In murine and human wt53-carrying cells, we showed that the impairment of the ERK2 cleavage by caspase inhibitors interfered with the ADR-induced G1 arrest, slowing down the exit from the cell cycle and determining a partial depletion of the G1 phase. These results indicate that the ERK2 cleavage participates in the p53-mediated mechanisms of G1 arrest.…”
Section: Erk2 Cleavage Is Required For P53 To Inhibit Cell Proliferationmentioning
confidence: 92%
“…DNA damage checkpoints control both the length of the cell cycle phase and the activation of DNA repair pathways, and movement of DNA repair proteins to the sites of DNA damage, thus helping to integrate DNA repair with cell cycle progression. 39,40 Disassociation of the checkpoints and DNA repair mechanisms can lead to apoptosis. [41][42][43][44] Reports from several laboratories, including ours, have shown that BCR/ABL-positive cells display pronounced G 2 /M delay in response to various chemotherapeutics, which seems to be an essential component in the resistance to DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…The second is a Tdp1-independent, checkpointdependent pathway involving the Rad9 human homologues in the checkpoint response and the removal of damage by the three parallel functioning endonucleases. Even though there is redundancy in the repair of Top1-mediated DNA damage, it may not be critical to the clinical relevance of Tdp1 inhibition, since it is well established that deficiencies in checkpoint mechanisms are a common feature in cancer cells [71]. For example, if cancer-related checkpoint inactivation arises, then Tdp1 becomes the principle source for the removal of Top1-mediated DNA damage (Fig.…”
Section: Rationale For Targeting Tdp1 For Cancer Therapymentioning
confidence: 99%